Populærmusik meIlem mundtlig og skriftlig kultur - Rørdam Larsen, Charlotte (Danish Yearbook of Musicology, 1994)
Popular Music between Orality and Literacy This article attempts to reassess the aesthetics of popular music and the definitions of orality and literacy introduced by Walter J. Ong in his book Orality and Literacy 1982. These originally literary concepts are translated into music. Modem popular music is seen as an expression of secondary orality (Ong), modem popular music is defined as music characterized by oral aesthetic (the well-known) although it may be preserved and redeveloped (literacy) by means of modem technology.